Meningkatkan Kemampuan Menulis Puisi Bebas Melalui Media Biografi Tokoh Siswa Kelas VIII MTs NU Umbul Sari Kabupaten OKU Timur - Herni Fitriani; Sugiarti Sugiarti (Jurnal Pembahsi (Pembelajaran Bahasa Dan Sastra Indonesia), 2016)
The problem in this research is how the use of media biographies can improve the ability to write free verse in class VIII MTs NU Bannerman Sari East OKU District. This study aims to improve the ability to write free verse through the medium of biography. The subjects were students of class VIII MTs NU Bannerman Sari totaling 34 students. This research is a class act carried out in three cycles. Data collection techniques used are tests and observation. The use of biographical media can improve the ability to write free verse class VIII MTs NU Bannerman Sari East OKU District each cycle is the first cycle had an increase of 23.53%, in the second cycle an increase of 26.47% from cycle 1 and cycle 3 had an increase of 29.41% from cycle 2 with an increasing average of 23.81%. Keywords: writing free verse biography media.